Accounting Education: a theoretical overview - REDDA, Khadidja; KHALFALLAH, Zakarya (Journal of Finance & Corporate Governance, 2021)
The main purpose of this paper is to highlight the Accounting Education as a real asset that must continually evolve in order to best prepare future professionals on accounting for the new requirements imposed by technology and globalization. To do this, a descriptive methodological approach has been deployed to present Accounting Education Standards (IESs), which are developed by the International Accounting Education Standards Board (IAESB). These standards are influencing Accounting Education and training worldwide. The goal of the IESs is to ensure that economic decision makers can rely on the competence of professional accountants regardless of the country where the accountants received their education and training. Two major lessons emerge from this study. On the one hand, that the organizational structure, globalization and technology impact the skills needs of the accountancy profession and, on the other hand, there is a gap between the training provided and the needs of the profession